Perubahan sosial dan impaknya terhadap pembentukan modal insan menurut Ibn Khaldun - Mohammad Kamil Abd Majid; Rahimin Afandi Abd Rahim (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
The article will focused upon the concept of social change-Human capital and its connection with the concept of Islam Hadhari. In order to achieve such objective, basically this article will evaluate the nation of human capital within the concept of Islam Hadhari through several grand theories proposed by Ibn Khaldun. Due to such reason, this article will be divided into several sections, including; first, the introduction of the study. Second, Ibn Khaldun and the theory of social change in human society. Third, an analysis of the nation of human capital – Islam Hadhari through several grand theories proposed by Ibn Khaldun. Fourth, summary and conclusion.